PENGARUH PEMAHAMAN WAJIB PAJAK, PELAYANAN APARAT PAJAK, SANKSI PERPAJAKAN DAN PREFERENSI RISIKO TERHADAP KEPATUHAN WAJIB PAJAK UKM (Studi Kasus UKM di Kecamatan Semarang Selatan) - Yenita Novi Susanti, 13.05.52.0069; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2017)
This research aims to examine empirically the influence of understanding taxpayers, service tax officials, tax penalties risk preferences on taxpayer compliance SMEs. The population in this research is the taxpayer of SMEs at South Semarang DistrictÂ as many as 90 SMEs located at 10 villages there are, Peleburan, Wonodri, Mugassari, Lamper Lor, Lamper Tengah, Lamper Kidul, Randusari, Bulustalan, Barusari, Peterongan. The method used is purposive sampling method, that is sample selection method based on ease, where this method choose samples from the population element that the data is easily obtained by the researcher. The result of this research is service of tax officer and risk preference does not have an effect on compliance of taxpayer of SMEs. Understanding taxpayers and tax sanctions affect the compliance of compulsory SMEs.Keywords: Understanding Taxpayers, Tax Service Services, Tax Sanctions, Risk Preferences, Taxpayer Compliance SMEs